Recent advances in 3D imaging, modeling, and reconstruction - Voulodimos, Athanasios 1984-; Doulamis, Anastasios (IGI Global, 2020)
"This book explores commonly used techniques in fields of 3D image reconstruction using digital image processing techniques from 2D images, computer vision, augmented reality and the accuracy methods for good practice recommendation in this field. It also explores the emerging 3D-depth sensors for mobile devices to perform 3D Structure extraction of the environment"--
Keywords: Three-dimensional imaging; Image reconstruction